Emotional Intelligence and Organizational Commitment of Faculty Members, Tribhuvan University - Lama, Padam Bahadur; Bhattarai, Kamal Raj; Chataut, Mukund (Journal of Development Review, 2023)
The purpose of this study is to measure the impact of emotional intelligence (EI) on organizational commitment of faculty members of Tribhuvan University (T.U.). A cross sectional data collected through a convenient sampling using structured questionnaires. A total of 384 valid questionnaire received from respondents and analyzed using inferential statistics. The findings of the study depicts that emotional intelligence of university faculty members has positive and significant impact on organizational commitment i.e. affective commitment. It indicates that university faculty who had higher levels of emotional intelligence displayed higher degrees of affective commitment. The results of this study will motivate University policy makers and academic personalities to understand the linkage of EI of university faculty members and their affective commitment for better decision making.